Resilience of tropical tree cover: The roles of climate, fire, and herbivory. (24th August 2018) - Staal, Arie; van Nes, Egbert H.; Hantson, Stijn; Holmgren, Milena; Dekker, Stefan C.; Pueyo, Salvador; Xu, Chi; Scheffer, Marten
Abstract: Fires and herbivores shape tropical vegetation structure, but their effects on the stability of tree cover in different climates remain elusive. Here, we integrate empirical and theoretical approaches to determine the effects of climate on fire‐ and herbivore‐driven forest‐savanna shifts. We analyzed time series of remotely sensed tree cover and fire observations with estimates of herbivore pressure across the tropics to quantify the fire–tree cover and herbivore–tree cover feedbacks along climatic gradients. From these empirical results, we developed a spatially explicit, stochastic fire‐vegetation model that accounts for herbivore pressure. We find emergent alternative stable states in tree cover with hysteresis across rainfall conditions. Whereas the herbivore–tree cover feedback can maintain low tree cover below 1, 100 mm mean annual rainfall, the fire–tree cover feedback can maintain low tree cover at higher rainfall levels. Interestingly, the rainfall range where fire‐driven alternative vegetation states can be found depends strongly on rainfall variability. Both higher seasonal and interannual variability in rainfall increase fire frequency, but only seasonality expands the distribution of fire‐maintained savannas into wetter climates. The strength of the fire–tree cover feedback depends on the spatial configuration of tree cover: Landscapes with clustered low tree‐cover areas are more susceptible to cross a tipping point of fire‐driven forest loss than landscapes with scattered deforested patches. Our study shows how feedbacks involving fire, herbivores, and the spatial structure of tree cover explain the resilience of tree cover across climates. Abstract : We integrate empirical and theoretical approaches to show how feedbacks involving fire, herbivores, and the spatial structure of tree cover explain the resilience of tree cover across climates in the tropics. We find that these feedbacks generate emergent alternative stable states in tree cover with hysteresis across rainfall levels. At lower rainfall levels, a herbivore–tree cover feedback dominates; at higher rainfall levels, a fire–tree cover feedback dominates, which depends strongly on rainfall seasonality.